Exploring the situational interface of translation and cognition - Ehrensberger-Dow, Maureen; Englund Dimitrova, Birgitta, 1946- (Benjamins current topics., 2018)
"The contributions of this volume explore the dynamics of the interface between the cognitive and situational levels in translation and interpreting. Until relatively recently, there has been an invisible line in translation and interpreting studies between cognitive research (e.g., into mental processes or attitudes) and sociological research (e.g., concerning organization, status, or institutions). However, rapid developments in translation and interpreting practices (professional, non-professional) have brought to the fore the need to rethink theoretical perspectives and to apply new research methods. The chapters in this volume aim to contribute to this discussion through conceptual and/or empirical research. Drawing on different theoretical and methodological frameworks, they offer insights into diverse translation and interpreting situations, in a number of different countries and cultures, and their consequences for individual and collective cognition. Originally published as special issue of Translation Spaces 5:1 (2016)"--